(Des)Construção em Hilal Sami Hilal: uma construção pela arte em tempos de destruição - Macedo, Jéssica Galon da Silva (Revista do Colóquio, 2023)
As an activity inherent to human beings, art has always been linked to the ills and advances of society. Therefore, taking a political stand is an assignment of every artist, despite the economic appeal that capitalism often imposes on the art market. Environmental problems triggered by the unbridled pursuit of economic progress in today's society have generated major world, social and health crises. To emphasize the role of the artist in building critical awareness, we analyzed works by the artist Hilal Sami Hilal, pointing to an art that stimulates the sensitivity of thinking about the other, nature and oneself as part of the same thing.Keywords: art, environment, conscience, duty.